2021
DOI: 10.1016/j.jseint.2020.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver and intraobserver agreement of three-dimensionally printed models for the classification of proximal humeral fractures

Abstract: Hypothesis This study aimed to examine whether three-dimensionally printed models (3D models) could improve interobserver and intraobserver agreement when classifying proximal humeral fractures (PHFs) using the Neer system. We hypothesized that 3D models would improve interobserver and intraobserver agreement compared with x-ray, two-dimensional (2D) and three-dimensional (3D) computed tomography (CT) and that agreement using 3D models would be higher for registrars than for consultants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…This supports that 3D models are not clinically useful for classifying proximal humerus fractures but the question remained unanswered if other classifications, such as the Hertel LEGO description system, or specific fracture characteristics would improve with 3D modeling [9]. Another study found moderate agreement (kappa = 0.47) among 14 assessors, but they also simplified the Neer classification to three categories (two-part, three-part, and four-part fractures) and assessed the 3D-printed models without additional radiographs or CT images [3]. Again, the question whether 3D fracture models would be useful for characterization and assessment of other fracture classification systems was left open.…”
Section: Agreement On Fracture Characteristics and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports that 3D models are not clinically useful for classifying proximal humerus fractures but the question remained unanswered if other classifications, such as the Hertel LEGO description system, or specific fracture characteristics would improve with 3D modeling [9]. Another study found moderate agreement (kappa = 0.47) among 14 assessors, but they also simplified the Neer classification to three categories (two-part, three-part, and four-part fractures) and assessed the 3D-printed models without additional radiographs or CT images [3]. Again, the question whether 3D fracture models would be useful for characterization and assessment of other fracture classification systems was left open.…”
Section: Agreement On Fracture Characteristics and Classificationmentioning
confidence: 99%
“…To date, one study found that agreement improved regarding the choice of treatment (nonoperative versus osteosynthesis versus arthroplasty) when proximal humerus fractures were assessed with 3Dprinted models [8]. Nonetheless, two studies showed that 3D-printed models improved agreement for the Neer and AO classification systems among both residents and attending surgeons, but did not reveal a difference between both groups [3,9]. Although they conducted valuable work, they did not account for characterization and other fracture classification systems.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated the benefits of 3D printed models among residents, such as improving interobserver reliability of a proximal humerus fracture classification system, compared with radiographs and CT alone. 24 Education level was stratified in each cohort to investigate whether there was an intercohort difference between levels of education and reported patient understanding of their injury and surgical plan. All responses were on a continuous scale of 0 (no understanding) to 100 (expert understanding).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated the benefits of 3D printed models among residents, such as improving interobserver reliability of a proximal humerus fracture classification system, compared with radiographs and CT alone. 24 …”
Section: Discussionmentioning
confidence: 99%
“…The reliability of assessing proximal humerus fracture patterns using widely-held classification systems such as that of Neer and Hertel based on plain radiographs has been fairly low, though the addition of advanced imaging such as two-dimensional (2-D) and three-dimensional (3-D) CT scans appears to improve both inter- and intraobserver reliability [4]. More recently, using 3D printed models alone in the surgical planning process has been found to improve interobserver reliability over plain radiographs and both 2D and 3D CT scans using the Neer system, though the observed agreement with the printed models was only moderate [2]. In these studies, where the kappa values using the guidelines of Landis and Koch were reported as “substantial” and “moderate,” respectively, we must recognize that a high proportion of cases will still be misclassified.…”
Section: Where Are We Now?mentioning
confidence: 99%